Seasonal and Coseismic Velocity Variation in the Region of L'Aquila From Single Station Measurements and Implications for Crustal Rheology. Issue 7 (26th June 2020) - Poli, Piero; Marguin, Valentin; Wang, Qingyu; D'Agostino, Nicola; Johnson, Paul
Abstract: We performed measurements of velocity variations for variable coda waves time lapse using empirical Green's functions reconstructed by autocorrelation of seismic noise recorded during a period of 17 years in the region of L'Aquila, Italy. The time lapse approach permitted us to evaluate the spatial (depth) dependence of velocity variation (dv/v). By quantitatively comparing the 17 years of dv/v time series with independent data (e.g., strain induced by earthquakes and hydrological loading), we unravel a group of physical processes inducing velocity variations in the crust over multiple time and spatial scales. We find that rapid shaking due to three magnitude 6+ earthquakes mainly induced near surface velocity variations. On the other hand, slow strain perturbation (period 5 years, in the preseismic period) associated with hydrological cycles, induced velocity changes primarily in the middle crust. The observed behavior suggests the existence of a large volume of fluid‐filled cracks exist deep in the crust. Our study highlights the possibility of using seasonal and multiyear perturbations to probe the physical properties of seismogenic fault volumes and shed new light into the depth‐dependent rheology of crustal rocks in the region or L'Aquila. Key Points: We characterise long and short term velocity variation during 17 years around L'Aquila region (Italy) We resolved the source of seismic velocity variation and exploit them to obtain the depth dependent cause of velocity variation in the crust We highlighted a strong sensitivity to strain perturbation isolated at depth